The Hidden Target - MacInnes, Helen, 1907-1985 (London Fontana Collins, 1982)
A young woman is innocently caught up in a terrorist organization that is under surveillance by an army major she once loved at age fifteen.
Keywords: Terrorists -- Terrorism -- Spy stories